Unveiling the Antimicrobial Potential of Terminalia chebula Fruits in Poultry Feed: A Natural Alternative for Enhanced Food Safety and Animal Health - Sivanantham, Srinivasan; Jegadeeshkumar, Dhanasekaran; Ragavi; Arun , S.; Ajithkumar, S.; Praveen , S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Background: Bacterial contamination of poultry feed poses a significant risk to both poultry and consumers. The use of antibiotics to combat microbial contamination in poultry has raised health concerns, emphasizing the need for alternative methods to ensure food safety. Aim: This study aimed to investigate the antimicrobial potential of Terminalia chebula fruits (T. chebula) as a feed additive in poultry production. The study sought to assess the effectiveness of T. chebula in eradicating poultry-associated microbes and explore its potential use as a feed additive. Methodology: The study involved the collection and extraction of T. chebula fruits, qualitative phytochemical studies, and the isolation of bacterial pathogens from poultry feed samples. The antimicrobial activity of T. chebula was determined using the agar well diffusion method. GCMS analysis was employed to identify various secondary metabolites present in T. chebula. Results: The qualitative phytochemical studies showed that methanol and chloroform extracts of T. chebula exhibited significant antimicrobial efficacy against both Gram-positive and Gram-negative bacteria. GCMS analysis revealed the presence of phytochemicals and fatty acid compounds that contributed to the antimicrobial activity of T. chebula. The study also found that T. chebula exhibited superior antibacterial activity compared to the chloroform extract. Implications: The study highlights the potential of T. chebula as a sustainable alternative to antibiotics in poultry feed. The use of T. chebula as a feed additive offers innovative solutions to ensure food safety, improve animal health, and reduce the reliance on antibiotics in poultry production.